Система дифузійних частинок із склеюванням змінної маси - Конаровський, В.В. (Український математичний журнал, 2010)
Сконструирована математическая модель бесконечной системы диффузионных частиц со взаимодействием, имеющих массу, которая влияет па коэффициент диффузии. Частицы начинают движение с некоторого стационарного распределения массы, движутся независимо до момента встречи, а затем склеиваются и их масса суммируется, после чего коэффициент диффузии изменяется обратно пропорционально корню квадратному массы. Показано, что масса, которая переносится частицами, также имеет стационарное распределение. We construct a mathematical model of an infinite system of diffusion particles with interaction whose masses affect the diffusion coefficient. The particles begin to move from a certain stationary distribution of masses. Their motion is independent up to their meeting. Then the particles become stuck and their masses are added. As a result, the diffusion coefficient varies as a function inversely proportional to the square root of the mass. It is shown that the mass transported by particles is also characterized by a stationary distribution.